ПРИНЦИП ПОСТРОЕНИЯ СИСТЕМЫ ОБЛАЧНЫХ СЕРВИСОВ - Романов, Александр Иванович; Дидух, Ярослав Станиславович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2017)
The principle of constructing a system of cloud services Cloud architecture is a system architecture of the software systems involved in the delivery of cloud computing, typically involves multiple cloud components communicating.